‘SUPERFICIES’ – RZYMSKIE KORZENIE PRAWA ZABUDOWY - Dyjakowska, Marzena (Zeszyty Prawnicze, 2016)
‘Superficies’: The Roman Origins Of The Right To Build Upon A Plot Of Land Summary The aim of this paper is to present the Roman origin of the right of superficies (the right to erect a building on a plot of land), which is the subject of a bill drafted by the Polish Civil Law Codification Committee. This right is to replace the institution of perpetual usufruct, which has been extant in Polish civil law since the 1960s. Superficies has been present in many European systems of law (for example in the Bürgerliches Gesetzbuch German Civil Code of 1896, and the Austrian law of 1919). The author compares the subject and object of the right in question, the legal situation of the superficiarius and the rights of the owner of the land in Roman law and in the Polish draft bill. The main difference between the Roman superficies and the right proposed in the draft bill is the deviation from the principle of accession (superficies solo cedit): under the Polish draft bill the superficiarius will become the owner of the building. Furthermore, the Roman superficies was perpetual; in Poland it will be constructed as temporary (30-100 years). Both rights (in Roman and Polish law) share many other similarities: they are hereditary, and the superficiarius is to pay the owner of the land. The conclusion which may be drawn is that Roman institutions can still inspire the contemporary legislator.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />